It's a Stampede to Brisgo - Hercules Incorporated (1940 Hercules Advertisements, 1940)
Advertisement for Brisgo, a trademarked depilatory compound manufactured and sold by the Hercules Powder Company for the cosmetic removal of hair from hog skin. The advertisement, published amidst the 1940 U.S. Presidential election, features a cartoon depiction of a hog convention lauding Brisgo as the best candidate to cleanly and efficiently dehair hogs root to tip. This advertisement was published in the June 22, 1940 issue of National Provisioner. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Hair removal products; Meat industry and trade; Hair--Removal; Chemical industry; Hercules Incorporated; Corporations; Naval stores; Advertising, Industrial